Pain Management and Substance Use Disorders: A Position Statement. Issue 1 (January 2023) - Sowicz, Timothy Joseph; Compton, Peggy; Matteliano, Deborah; Oliver, June; Strobbe, Stephen; St. Marie, Barbara; Turner, Helen N.; Wilson, Marian
Abstract: The American Society for Pain Management Nursing and the International Nurses Society on Addictions hold the position that persons with co-occurring pain and substance use disorder have the right to be treated with dignity and respect and receive evidence-based, high-quality assessment and management for both conditions using an integrated, holistic, multidimensional approach. Nonopioid and nonpharmacological approaches to pain management are recommended. Opioids should not be withheld from anyone if necessary to treat pain, and a team-based approach, including pain and addiction specialists, should be utilized when possible. Pain management should include interventions aimed at minimizing the risk for relapse or escalation of problematic substance use and actively involve the person and their support persons in the plan of care. Institutions should establish policies and procedures that support this position statement.